INTEGRASI KURIKULUM ALAM DAN KURIKUKULUM MERDEKA DI SEKOLAH DASAR - Adha, Nurul; Suriansyah, Ahmad; Mulya Budi Harsono, Arta (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
The integration of the national curriculum with nature-based curricula remains a challenge for nature-based schools, particularly during the transition to the Merdeka Curriculum. This study aims to describe the integration of the Nature Curriculum and the Merdeka Curriculum at SD Alam Aisyiyah Banua Anyar Banjarmasin and to analyze its impact on students’ learning and character development. This research employed a qualitative approach with a case study design. Data were collected through semi-structured interviews, non-participant observation, and documentation, with a single nature-based elementary school as the unit of analysis. The findings indicate that curriculum integration is carried out by aligning the learning outcomes of the Merdeka Curriculum with the four pillars of the Nature Curriculum morality, logic, leadership, and entrepreneurship. Learning takes place contextually in both classroom and outdoor settings. This integration enhances students’ enthusiasm, independence, responsibility, and awareness of moral and environmental values. The study concludes that the integration of the two curricula fosters active, meaningful, and character-oriented learning, and it offers relevant insights for developing adaptive curriculum models in nature-based schools.